Effects of intravenous and inhalation induction of anesthesia on oxygen delivery in elderly patients undergoing colorectal surgery - Dušan Mekiš; Vesna Sok (Acta Medico-Biotechnica, 2021)
Purpose: The induction of anesthesia with direct laryngoscopy and orotracheal intubation are two interventions, which can influence oxygen delivery. Rapid adjustments of treatment to restore oxygen delivery are crucial to improving the outcomes for patients. The aim of this study was to compare the effects of induction of anesthesia with propofol and sevoflurane on oxygen delivery in elderly patients undergoing colorectal surgery. Methods: We studied forty patients with physical status II or III, according to the American Society of Anesthesiology,who were older than 65 years and undergoing elective surgery for resection of colorectal carcinoma. The patients were randomly divided into the propofol group (P-group) and sevoflurane group (S-group), according to the anesthetic received for the induction of anesthesia. Results: After induction of anesthesia, heart rate, mean arterial pressure, cardiac output and the oxygen delivery index significantly decreased in both groups compared to the baselinevalues. Following induction of anesthesia, the decrease in heart rate was significantly more rapid in the P-group. Immediately after orotracheal intubation, heart rate, mean arterial pressure, cardiac output and the oxygen delivery index significantly increased in the S-group, but one minute later these diferences were not statistically significant. Heart rate, meanarterial pressure, cardiac output and the oxygen delivery index were significantly lower after orotracheal intubation in both groups, compared to baseline.Conclusion: Prpofol and sevoflurane are clinically comparable in the induction of anesthesia in elderly patients according to the effect on oxygen delivery.